2008
DOI: 10.1111/j.1600-0560.2007.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic fibroblastoma: a case presenting as a protruding nodule in the dermis

Abstract: Diffuse malignant peritoneal mesothelioma (DMPM) is a relatively rare neoplasm. Risk factors associated with its development include asbestos exposure, chronic irritation or inflammation of the peritoneum, abdominal radiotherapy, familial Mediterranean fever and simian virus 40. A familial segregation of this neoplasia has been reported in small villages of the Cappadocian region of Turkey, and it has been postulated that hereditary factors may predispose to mesothelioma, even with exposure to small amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In many previously reported cases, tumors were found to penetrate the gluteal muscle, with 1 case of extension to the bony pelvis [35]. Similarly, in our series, 1 patient (case 12) presented with osteolysis of the sacrum as a consequence of tumoral infiltration.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In many previously reported cases, tumors were found to penetrate the gluteal muscle, with 1 case of extension to the bony pelvis [35]. Similarly, in our series, 1 patient (case 12) presented with osteolysis of the sacrum as a consequence of tumoral infiltration.…”
Section: Discussionmentioning
confidence: 58%
“…This complication is uncommon: since 1958 only 52 cases have been published, most often as case reports – 27 cases were reported in a review in 1995 [15], which omitted 3 additional ones reported up to that time period [16,17,18], 22 additional cases were then published from 1995 to 2008 [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36]. Lapins et al [37] reported 5 cases of ‘nonmelanoma skin cancer’ among a cohort that may contain some patients who did not have criteria for HS so we did not include those results.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis claims that collagen production is induced by tumour cells, which cause activation of [73][74][75][76] ( Figure 5A Desmoplasia: not always a bad thing 647 fibroblasts and subsequent proliferation. 2,[6][7][8]14 This mechanism is also believed to promote the growth and invasiveness of tumours.…”
Section: Stromal Reactive Patternmentioning
confidence: 99%
“…Most of the reported cases have been located in the deep subcutaneous tissue, fascia or skeletal muscle. Dermal involvement, as seen in this case, is extremely rare . This neoplasm has been reported at various locations, including the arms, legs, chest wall, abdominal wall, upper back, neck, forehead and mucosal areas .…”
Section: Discussionmentioning
confidence: 58%